Pediatric melioidosis in Sarawak, Malaysia: Epidemiological, clinical and microbiological characteristics. - Anand Mohan; Yuwana Podin; Nickson Tai; Chae-Hee Chieng; Vanessa Rigas; Barbara Machunter; Mark Mayo; Desiree Wong; Su-Lin Chien; Lee-See Tan; Charles Goh; Reginal Bantin; et al. (Public Library of Science (PLoS), 2017)
Melioidosis is a serious, and potentially fatal community-acquired infection endemic to northern Australia and Southeast Asia, including Sarawak, Malaysia. The disease, caused by the usually intrinsically aminoglycoside-resistant Burkholderia pseudomallei, most commonly affects adults with predisposing risk factors. There are limited data on pediatric melioidosis in Sarawak.A part prospective, part retrospective study of children aged <15 years with culture-confirmed melioidosis was conducted in the 3 major public hospitals in Central Sarawak between 2009 and 2014. We examined epidemiological, clinical and microbiological characteristics.Forty-two patients were recruited during the 6-year study period. The overall annual incidence was estimated to be 4.1 per 100,000 children <15 years, with marked variation between districts. No children had pre-existing medical conditions. Twenty-three (55%) had disseminated disease, 10 (43%) of whom died. The commonest site of infection was the lungs, which occurred in 21 (50%) children. Other important sites of infection included lymph nodes, spleen, joints and lacrimal glands. Seven (17%) children had bacteremia with no overt focus of infection. Delays in diagnosis and in melioidosis-appropriate antibiotic treatment were observed in nearly 90% of children. Of the clinical isolates tested, 35/36 (97%) were susceptible to gentamicin. Of these, all 11 isolates that were genotyped were of a single multi-locus sequence type, ST881, and possessed the putative B. pseudomallei virulence determinants bimABp, fhaB3, and the YLF gene cluster.Central Sarawak has a very high incidence of pediatric melioidosis, caused predominantly by gentamicin-susceptible B. pseudomallei strains. Children frequently presented with disseminated disease and had an alarmingly high death rate, despite the absence of any apparent predisposing risk factor.